DIFFERENCES IN THE EFFECTIVENESS OF THE DIRECT DEMONSTRATION METHOD AND VIDEO SCREENING OF FIRST AID IN TRAFFIC ACCIDENTS ON THE INCREASE IN KNOWLEDGE OF SENIOR HIGH SCHOOL STUDENTS - Yustina Ni Putu Yusniawati; I Wayan Agus Maharyawan; Ahmad Robani (Nurse and Health: Jurnal Keperawatan, 2020)
Background: Traffic accidents are unpredictable collisions among vehicles that might lead to casualties. Injuries due to traffic accidents have killed at least 1.2 million lives per year. Fatalities are high as first aid is not properly administered, causing to higher mortality rate.Objectives: This research compared the effectiveness between the use of live demonstration and videos on high school students’ first aid knowledge.Methods: The research was conducted in the form of a comparative study with a cross sectional approach, for three months, starting from March to June 2019 in Senior High School 1 Rendang Karangasem Bali. The sample taken as many as 150 people as respondents who were divided into 2 groups, namely group 1 attended counseling which featured live demonstrations, while group 2 attended counseling where video was used as a medium. The instrument used was a questionnaire modified by researchers from Gorucu-Coskuner, H., Atik, E., & Taner, T. (2020) with 24 question items with yes and no answers. The validity test was carried out using the Pearson product-moment bivariate correlation technique where these results indicate that the value of "r count" (0.873)> "r table (0.227) means that the questionnaire is valid. Reliability test using alpha technique (Cronbach's) obtained r count (0.919)> "r alpha" (0.227) then the questionnaire was declared fit for use. Furthermore, bivariate analysis was carried out by comparing the knowledge of the two groups using the Mann-Whitney analysis.Results: A meaningful difference was found between the use of live demonstration and videos at P <α = 0.05 and p = 0,000. The mean score of the pretest done in group 2 was 96.70, while the one of the groups 1 was 48.30 which scores increased in the posttest to 105.39 and 39.61.Conclusion: Therefore, the use of video media has been found more effective than the use of live demonstrations in improving students’ first aid knowledge. Based on this finding, it is considered necessary to create more tutorial videos to improve first aid knowledge of the community especially students. Keywords: Counseling, Demonstration, Video, First Aid, Traffic Accident.